Description of the usefulness and ease of use wireless stethoscope for auscultation: A pilot study - Ricky Prawira; Suhartini Ismail; Andrew Johan; Rifky Ismail (Alma Ata University Press, 2023)
Background: A stethoscope is an acoustic medical device commonly utilized for listening to internal sounds in the human body. Since its invention, the stethoscope has undergone several transformative improvements, including the introduction of electronic systems in the last two decades. Through the Center of Excellence in the Higher Education of Science and Technology (PUI-PT), Center for Bio Mechanics, Bio Material, Bio Mechatronics, and Bio Signal Processing (CBIOM3S), the Diponegoro University has developed a wireless stethoscope to enable the user to examine the patients quickly without being constrained by tubing, unlike the manual stethoscope. The wireless stethoscope supports health workers in performing their work. This new technology creates various perceptions from its users, one of whom is nurses. Objectives: This study aims to provide an overview of nurses' perceptions regarding the usefulness and ease of use of a wireless stethoscope to perform auscultation of the heart and lungs of critically ill patients. Methods: The research method employed was a pilot study, and 40 nurses working in the critical care units, including the Intensive Care Unit, High Care Unit, and Stroke Unit in a private hospital in Palembang City, were chosen as respondents for a total sampling technique. Results: Nurses' perceptions of the ease and usefulness of a wireless stethoscope were measured using the perceived usefulness and perceived ease of use questionnaires. The nurses' perception of the use of wireless stethoscopes exhibited a mean score of 4.27, while the nurses' perception of the ease of use of wireless stethoscopes showed a mean score of 4.35. Those results indicate that nurses in the critical care units accepted wireless stethoscopes in terms of ease of use and usefulness as a device for performing auscultation of the heart and lungs of critically ill patients. Conclusions: Nurses get new technology like a wireless stethoscope because it can work more quickly and is easy to use thereby assisting nurses in conducting cardiac and pulmonary auscultation in critical patients.